Plant proteostasis: a proven and promising target for crop improvement. Issue 2 (5th August 2022) - Theodoulou, Frederica L.; Orosa-Puente, Beatriz; Trujillo, Marco; Rubio, Vicente
Abstract: The Green Revolution of the 1960s accomplished dramatic increases in crop yields through genetic improvement, chemical fertilisers, irrigation, and mechanisation. However, the current trajectory of population growth, against a backdrop of climate change and geopolitical unrest, predicts that agricultural production will be insufficient to ensure global food security in the next three decades. Improvements to crops that go beyond incremental gains are urgently needed. Plant biology has also undergone a revolution in recent years, through the development and application of powerful technologies including genome sequencing, a pantheon of 'omics techniques, precise genome editing, and step changes in structural biology and microscopy. Proteostasis – the collective processes that control the protein complement of the cell, comprising synthesis, modification, localisation, and degradation – is a field that has benefitted from these advances. This special issue presents a selection of the latest research in this vibrant field, with a particular focus on protein degradation. In the current article, we highlight the diverse and widespread contributions of plant proteostasis to agronomic traits, suggest opportunities and strategies to manipulate different elements of proteostatic mechanisms for crop improvement, and discuss the challenges involved in bringing these ideas into practice.